Genomic analyses overturn two long‐standing homoploid hybrid speciation hypotheses. (1st July 2021) - Goulet‐Scott, Benjamin E.; Garner, Austin G.; Hopkins, Robin
Abstract: The importance of hybridization in generating biological diversity has been historically controversial. Previously, inference about hybridization was limited by dependence on morphological data; with the advent of the next‐generation sequencing tools for nonmodel organisms, the evolutionary significance of hybridization is more evident. Here, we test classic hypotheses of hybrid origins of two species in the Phlox pilosa complex. Morphological intermediacy motivated the hypotheses that Phlox amoena lighthipei and Phlox pilosa deamii were independent homoploid hybrid lineages derived from P. amoena amoena and P. pilosa pilosa . We use double‐digest restriction site‐associated DNA sequencing of individuals from throughout the range of these taxa to conduct the most thorough analysis of evolutionary history in this system to date. Surprisingly, we find no support for the hybrid origin of P. pilosa deamii or P. amoena lighthipei . Our data do identify a history of admixture in individuals collected at a contemporary hybrid zone between the putative parent lineages. We show that three very different evolutionary histories, only one of which involves hybrid origin, have produced intermediate or recombinant morphological traits between P. amoena amoena and P. pilosa pilosa . Although morphological data are still an efficient means of generating hypotheses about past gene flow, genomic data are now the standard of evidence for elucidating evolutionary history.